Pembuatan Referensi Praktik Dasar Perancangan Progressive Die pada Perangkat Lunak Siemens NX - Suseno, Ignatius; Sutopo, Antonius Adi; Rizaldi S, Fajar (Jurnal Teknik Mesin, 2025)
As a continuous improvement through state-of-the-art discovery and uniqueness for the learning material of the Progressive Die Design practical lecture, it is necessary to update it by reviewing 2 aspects, namely "knowledge of how to design progressive die" and "its application to Siemens NX software". Knowledge is obtained by comparing design methods from several selected sources and producing logical progressive die design operation guidelines in sequence. The application on Siemens NX uses the Siemens NX feature optimization method to produce the best design in a relatively short time, with the guidance of design knowledge that previously obtained. An example of a fairly complex sheet metal product is selected as an object for progressive die design. This design requires the selection and combination of Siemens NX features to produce the stages of operation planning, strip development and die designing. The difference sheet metal geometric complexity will result a different number of stages due to the uniqueness of the alternative features selection and combinations. The knowledge and application of design process are documented into a tutorial reference book and tested on students with a feasibility result above 90%. Eligibility data was obtained by filling out a questionnaire after studying the reference book.